2022
DOI: 10.3389/fpsyg.2022.922404
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Unhappy Musicians, Resistance Toward Innovation and Uncreative Music Products: Psychological Security as Moderator

Abstract: Recently, uncreative music products have become a global issue due to the unhappy musicians and resistance to innovation that needs researchers’ focus. This article explores the impact of unhappy musicians and resistance to innovation on uncreative music products in Malaysia. This article also investigates the moderating role of psychological security among the relationships of unhappy musicians, resistance to innovation, and uncreative music products in Malaysia. This study has applied the questionnaire metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…This research adds to the body of knowledge in a number of important ways. To begin, this research has never been done before in this field and has huge implications for SMFE financial professionals, business owners, and accountants, as well as for legislators (Liang, 2022). This research will help them make informed decisions by revealing which methods of financial management will most positively impact their company' expansion and development.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research adds to the body of knowledge in a number of important ways. To begin, this research has never been done before in this field and has huge implications for SMFE financial professionals, business owners, and accountants, as well as for legislators (Liang, 2022). This research will help them make informed decisions by revealing which methods of financial management will most positively impact their company' expansion and development.…”
Section: Research Questionsmentioning
confidence: 99%
“…Studies on capital budgeting have been conducted for decades. According to (Liang, 2022) conducted the first research on working capital for SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the studies on distance education students are examined, it is stated that students generally find oral presentations useful in distance education and they have a negative attitude towards synchronous lessons (Karatepe et al, 2020;Ghahderijani et al, 2021), on the other hand, access to courses originating from internet and technical problems, They prefer distance education (Ozyurek, 2016;Sercemely&Kurnaz, 2020) and they find distance education more economical (Olcay, &Doy, 2016;Liang et al, 2022). In another study conducted by Yildiz (2020), taking the opinions of undergraduate students, the students stated that the most important elements for an effective distance education are instructor, student characteristics, instructional design, teaching method, interaction, cooperation and orientation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ferdig (2007) also discussed significance of social media, pointing out that contact is both required and beneficial while the process of learning a language. An efficient strategy for introducing new concepts and terminology is necessary for a good lesson (Liang, Akhter, & Kumar, 2022). It has been shown that in order to properly teach anything, it must be done so in a systematic and logical manner that favours learners.…”
Section: Introductionmentioning
confidence: 99%